Analysis of lipid, glycemic and feeding profile of community health workers after the intervention to promote self-care - Bentes Araújo Rodrigues, João Guilherme (2024)
Introduction: Healthy eating is the result of a process that can be influenced by several factors and can be a challenge even for health professionals. The objective of this study was to evaluate the eating behavior of community health agents (ACS) after their participation in a self-care course. Methodology: Quantitative study, of the research-intervention type, with 55 ACS of the municipality of Assaré, Ceará, Brazil. The intervention was carried out in April and July 2022, making a total of 16 hours. The participants appropriated the contents and exercised the simulation of dishes with meals that they could produce according to their conditions and access. Data collection was performed before and after the intervention, such as the Food Consumption Markers Form, 24-hour Food Recall (RA-24H) and blood collection to assess the lipid and glycemic profile. The stage of behavior change by the light of the Transtheoretical Model was also verified. Results: There was an improvement in eating habits and a reduction in biochemical markers (total cholesterol and fractions, triglycerides and fasting glucose), with a significant difference in glycosylated hemoglobin (p<0.0001). There was an increase in the consumption of beans, fruits and vegetables, with a reduction in the consumption of processed (p = 0.01) and ultra-processed (p = 0.001). Most ACS (60%) were in the action stage for healthy eating. Conclusions: The intervention sensitized ACS for self-care, contributing to healthier behaviors.